Study of silane layers grown on steel and characterized using ellipsometry at different wavelength and incidence angles - Deyá, Marta Cecilia (2013)
The γ-mercaptopropyl trimethoxysilane (MPTMS) has two reactive groups: the metoxi (-OCH3) which hydrolyses and form covalent bounds with both the siloxane network and the surface oxide of ferric alloys, and a second reactive tiol group (SH), which reacts forming strong covalent bounds with Ag, Au, Pt y Cu. The layers grown by hydrolysis and condensation are used as “primer” for the adhesion of anticorroding coatings. On the other hand MPTMS is also used in different applications as sensors, and microelectronic.